El Salvador : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
This paper analyzes economic developments in El Salvador during 1990-97. The paper assesses the prospects of the Salvadoran economy in facing the new challenges coming from its reinsertion into the global economy. The paper describes the evolution of trade competitiveness and evaluates the divergence from equilibrium of the real effective exchange rate. It concludes that the exchange rate behavior in the last decade appears to have followed roughly the path predicted by a long-term equilibrium exchange rate model consistent with a current account deficit of about 2 percent of GDP.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet